CLOZAPINE INDUCED NEUTROPHIL CYTOTOXICITY IN SCHIZOPHRENIC PATIENTS. - AFSHAN ZEESHAN WASTI; NIKHAT AHMED (International Journal of Pharma and Bio Sciences, 2013)
The risk of potentially life threatening idiosyncratic reactions, limited the use of clozapine therapy, in the treatment refractory schizophrenia. The present study aims to investigate the neutrophil cytotoxicity in the clozapine treated schizophrenic patients, as it is still prescribed frequently for psychiatric patients in Pakistan. The assessment was focused on the hematological and absolute indices; serum iron profile, cell viability and morphological examination of peripheral blood smear, in the clozapine treated schizophrenic patients (n=56) by using standardized laboratory techniques and automated analyzers. The striking finding is the presence of neutrophil cytotoxicity; observed most frequently in the peripheral blood smear of the clozapine treated patients. All the stages of cytotoxic effect like vacculation in cytoplasm, nuclear fragmentation and chromatolysis was observed in the neutrophil during differential counting with significant decrease in neutrophil count suggesting agranulocytosis. Our data, raised concerns about hematological side effects of clozapine treatment in order to provide hematological safety leading to decrease morbidity and mortality related with this drug.